Treating seizures and epilepsy with anticoagulants? - Maggio, Nicola; Blatt, Ilan; Vlachos, Andreas; Tanne, David; Chapman, Joab; Segal, Menahem (Frontiers in Cellular Neuroscience, 2013)
Thrombin is a serine protease playing an essential role in the blood coagulation cascade. Recent work, however, has identified a novel role for thrombin-mediated signaling pathways in the central nervous system. Binding of thrombin to protease-activated receptors (PARs) in the brain appears to have multiple actions affecting both health and disease. Specifically, thrombin has been shown to lead to the onset of seizures via PAR-1 activation. In this perspective article, we review the putative mechanisms by which thrombin causes seizures and epilepsy. We propose a potential role of PAR-1 antagonists and novel thrombin inhibitors as new, possible antiepileptic drugs.